2011
DOI: 10.1021/jp201035g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Decomposition of BCl3 Induced by a H Radical

Abstract: We report on a theoretical study of the gas-phase decomposition of boron trichloride in the presence of hydrogen radicals using ab initio energetic calculations coupled to TST, RRKM, and VTST-VRC kinetic calculations. In particular, we present an addition-elimination mechanism (BCl(3) + H → BHCl(2) + Cl) allowing for a much more rapid consumption of BCl(3) than the direct abstraction reaction (BCl(3) + H → BCl(2) + HCl) considered up to now. At low temperatures, T ≤ 800 K, our results show that a weakly stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…Path sampling with Ab Initio molecular dynamics has been used before for the study of water autoionization, 42 fenton reactions, 43 gas-phase decomposition reactions, 44 and enzyme catalysis. 45 However, these papers are based on the original TPS 39 algorithm employing a single path ensemble of reactive trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Path sampling with Ab Initio molecular dynamics has been used before for the study of water autoionization, 42 fenton reactions, 43 gas-phase decomposition reactions, 44 and enzyme catalysis. 45 However, these papers are based on the original TPS 39 algorithm employing a single path ensemble of reactive trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7b shows that the logarithm of the decreasing rate for BCl 3 It should be noted that Ref. [40] reported a H radical attacking step of addition-elimination mechanism H+BCl 3 → BHCl 2 +Cl for the consumption of BCl 3 and the production of Cl radical and BHCl 2 (our IM33). This mechanism might also be important in our reaction system.…”
Section: Apparent Activation Energymentioning
confidence: 81%
“…In Ref. [40], mechanisms of addition-elimination (AE) and direct abstraction (DA) of Cl atom in BCl 3 +H were investigated theoretically in detail to address the reaction of BCl 3 and the H radical that can be compared with an experimental observation at a condition of H at 2 Torr pressure. The present work has not involved this step mainly because we regard reaction (12) as the initialization for B production and the fact that H 2 has a much higher concentration than Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their rate constants were calculated for temperatures within 200-2000 K and adopted G45-G58 [29]. Reinisch et al [30] reported a set of theoretical experiments of the gas-phase decomposition of boron trichloride in the presence of hydrogen radicals, and their reactions are also included (G59-G62 in Table 3). Note: The rate constants are written according to Arrhenius equation: K = AT n e −E/RT .…”
Section: Model Simulation and Prediction 2 1 Reactor-scale Modelmentioning
confidence: 99%